Fecal microbiota transplantation for antibiotic resistant bacteria decolonization. (June 2020) - Amrane, Sophie; Lagier, Jean-Christophe
Abstract: Patients colonized with antibiotic resistant bacteria are at risk of infections and spontaneous decolonization delays are highly variable between patients. The management of these patients is therefore time-consuming; requires patient isolation, and cohort policies. Fecal microbiota transplantation (FMT) has been used with the aim of shortening this gut colonization. Here, we proposed a comprehensive literature review on FMT utilization for gut antibiotics resistant bacteria decolonization. After literature research through Pubmed indexed for MEDLINE, we analyzed 23 studies with description of FMT utilization and analyze of gut decolonization. In total, the data involved 197 patients, 153 of whom underwent FMT. Overall, 66.7% (102/153) of the patients were decolonized after FMT. However, we noticed a lot of interpretation bias, such as variation in colonization definition and high disparities in FMT administration modalities. Two disparities were of special interest: repeated FMT seems to increase the effectiveness of decolonization, and gut decolonization with antibiotics before FMT was proposed by some authors, but with too few studies to draw a conclusion. Overall, the use of FMT is a promising perspective for intestinal decolonization, but it requires greater standardization.